CTAB-Assisted Synthesis of C@Na3V2(PO4)2F3 With Optimized Morphology for Application as Cathode Material for Na-Ion Batteries - Criado, Ana; Lavela, Pedro; Ortiz, Gregorio F.; Tirado, José L.; Gzouli, Somaya; Edfouf, Zineb; Pérez-Vicente, Carlos (Frontiers in Physics, 2019)
C@Na3V2(PO4)2F3 samples were obtained by using Cetyl Trimethyl Ammonium Bromide (CTAB) as a surfactant. The optimization of the added amount allowed controlling the eventual nanometric morphology of the particles. The morphological and structural properties of these samples were discussed in the light of solid-state techniques as X-ray diffraction, Raman and XPS spectroscopies, and electron microscopy. Galvanostatic test in sodium half-cells revealed that the nanometric spherical and porous particles provided by the addition of intermediate amounts of CTAB showed excellent cycling stability and superior high rate capability reflected in the minimization of the cell polarization and the determination of a high apparent diffusion coefficient.